A Comparison of the Current N2 Classification and a Modified N2 Categorization in TNM Staging of Esophageal Cancer Patients - Xi, Kexing; Yu, Hui (Frontiers in Oncology, 2021)
Objective To compare the effectiveness of the current N classification and a modified N2 categorization in TNM staging of esophageal cancer (EC) patients. Methodology A total of 2753 EC patients were enrolled in the study: 2283 EC patients from the Surveillance, Epidemiology, and End Results (SEER) database and 470 separate Chinese patients were used to verify the results of the SEER database. X-tile software was employed to determine the optimal cutoff points of the number of metastatic lymph nodes (LNs) in the N2 category. Univariate and multivariate Cox regression analyses were performed to identify the survival risk factors. Result Patients in the N2 category were divided into two groups based on the number of metastatic LNs. Patients with three and four metastatic LNs were categorized as N2a, while those with five and six metastatic LNs were categorized as N2b. The 3-year overall survival (OS) rate in the SEER database was 71.5%, 42.3%, 23.6%, 17.2%, and 10.7% for patients with N0, N1, N2a, N2b, and N3, respectively (P<0.001). Furthermore, a separate Chinese cohort was enrolled to validate the revised N2 category. Additionally, the 3-year OS rate was 71.5%, 42.3%, 23.6%, 17.2%, and 10.7% for patients with N0, N1, N2a, N2b, and N3, respectively (P<0.001). Conclusion The current N2 category should be further divided into two groups (N2a and N2b) to provide more accurate prognosis information that could further help in developing personalized therapeutic strategies.